Flexible PDMS microparticles to mimic RBCs in blood particulate analogue fluids. (September 2019) - Pinho, D.; Muñoz-Sánchez, B.N.; Anes, C.F.; Vega, E.J.; Lima, R.
Highlights: Blood analogue fluids should match the rheology of blood at both macro and microscale level. Development of Polydimethylsiloxane (PDMS) microparticles with similar properties to RBCs. The deformability of PDMS microparticles are compared against RBCs. The proposed particles replicate RBCs in terms of deformability, steady shear viscosity and cell-free layer phenomenon. Abstract: Polydimethylsiloxane (PDMS) has a wide variety of commercial and industrial applications due to its mechanical and rheological properties in a range similar to the living tissues. In this study, we demonstrate that PDMS can be used to produce deformable microparticles to be integrated in the development of particulate blood analogue fluids. The difficulties associated with the use of in vitro blood make it necessary to perform in vitro experiments of blood flow with blood analogue fluids. However, an ideal analogue must match the rheology of blood at several points, and for that, blood analogue fluids should be a suspension of microparticles with similar properties (size, shape and flexibility) to blood cells, in particular to the red blood cells (RBCs). The microparticles used in this study were produced from a transparent PDMS with crosslinking ratios of 10:1, 8:2 and 6:4; from a black PDMS with a ratio of 1:1 and from a red-pigmented PDMS. Each PDMS microparticles sample was suspended in Dextran 40 to perform deformability assays and cell-free layer analysis in a hyperbolic-shaped microchannel and steady shear viscosity measurements in a rheometer. The proposed microparticles suspensions show a great potential to mimic the structural and rheological properties of RBC suspensions and consequently to develop blood analogue fluids with rheological properties similar to real blood.